Perception of change communication factors between executive and non-executive in a restructuring exercise - Abdullah, Mohammad Firdaus Low; Wok, Saodah; Ghazali, Ruziah (2015)
The objective of this study is to differentiate between executives' and non-executives' change communication factors (consisted of receiving information, quality of information, involvement in decision making and leader's vision) in a selected organization for restructuring. Kurt Lewin's theory of effective communication was used. Data were gathered from 87 executives and 276 non-executives in a selected telecommunications company. A set of self-administered questionnaires was used to gather the data. T-test was used to differentiate the results from executives and non-executives on the change communication factors during the restructuring exercise. The study found that only one change factor, namely Receiving information' produced significant difference between the executives and non-executives through the study.